Pop corn - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Senegalese farmers have shifted en masse, to a man, and to a woman, from groundnuts to maize for the 2002 season. The falling prices and demand for groundnut, together with privatisation, the closure of the statal main buyer Sonagrains and the lack...